2024
DOI: 10.1146/annurev-arplant-070623-093110
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodesmata: Channels Under Pressure

Emmanuelle M. Bayer,
Yoselin Benitez-Alfonso

Abstract: Multicellularity has emerged multiple times in evolution, enabling groups of cells to share a living space and reducing the burden of solitary tasks. While unicellular organisms exhibit individuality and independence, cooperation among cells in multicellular organisms brings specialization and flexibility. However, multicellularity also necessitates intercellular dependence and relies on intercellular communication. In plants, this communication is facilitated by plasmodesmata: intercellular bridges that allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…Maintenance of PDs could be necessary to allow symplastic flow of information from surrounding somatic cells to the meiocytes (Heslop-Harrison, 1964 & 1966; Heslop-Harrison& Mackenzie, 1967; Plackett et al 2014; Liu et al 2017, Zhai et al 2015) and/or, the other way around, from sexual cells to somatic cell layers (Yang et al 1999). Although the nature of the symplastically mobile molecules has not been yet identified, PDs are pathway for transcription factors, hormones and RNAs (including silencing signals) that regulate important developmental transitions, including stomata cell fate transition (Cui et al, 2023), lateral root initiation (Benitez-Alfonso et al, 2013), among others (Bayer and Benitez-Alfonso, 2024). A recent review, mentioned transcription factors involved in microsporogenesis in Arabidopsis, several of which are strong candidates for mobile proteins (Wiese et al, 2024) and should be targeted in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of PDs could be necessary to allow symplastic flow of information from surrounding somatic cells to the meiocytes (Heslop-Harrison, 1964 & 1966; Heslop-Harrison& Mackenzie, 1967; Plackett et al 2014; Liu et al 2017, Zhai et al 2015) and/or, the other way around, from sexual cells to somatic cell layers (Yang et al 1999). Although the nature of the symplastically mobile molecules has not been yet identified, PDs are pathway for transcription factors, hormones and RNAs (including silencing signals) that regulate important developmental transitions, including stomata cell fate transition (Cui et al, 2023), lateral root initiation (Benitez-Alfonso et al, 2013), among others (Bayer and Benitez-Alfonso, 2024). A recent review, mentioned transcription factors involved in microsporogenesis in Arabidopsis, several of which are strong candidates for mobile proteins (Wiese et al, 2024) and should be targeted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation rather supports the hypothesis that callose renders transient stability to PDs during mitosis-meiosis initiation. The properties of callose at PD-associated cell walls has been questioned recently (Abou-Saleh et al 2018; Amsbury et al, 2018; Bayer and Benitez-Alfonso, 2024), and changes in its role in PD formation likely depend on cell wall composition. We showed that cellulose content remains unaltered in both Osgsl5-2 and Osgsl5-3 pre-meiotic and early meiotic prophase I anthers, thus depletion of callose might correlate with a hydrogel model where high cellulose:callose ratio increases cell wall stiffness (Abou-Saleh et al 2018), potentially affecting the formation (by cell wall digestion) of new PDs.…”
Section: Discussionmentioning
confidence: 99%